2004
DOI: 10.1097/01.mlr.0000124254.88292.a1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Comorbidity Indices for Patients With Head and Neck Cancer

Abstract: Both the general and disease-specific comorbidity indices provided important prognostic information. The disease-specific indices did not perform better than the general indices. In this claims-based analysis, there was no apparent advantage to using a disease-specific index when attempting to predict overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 20 publications
1
44
0
3
Order By: Relevance
“…Radiation oncologists provided information on the primary tumor: site, dimensions, and clinical tumor-node-metastasis stage. Comorbidities were assessed using the Charlson comorbidity index (36). Follow-up visits with study nurses and radiation oncologist were scheduled immediately at the end of the radiation therapy, 1 month later, and then every 6 months for the first 3 years followed by once a year until the end of the study (June 30, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Radiation oncologists provided information on the primary tumor: site, dimensions, and clinical tumor-node-metastasis stage. Comorbidities were assessed using the Charlson comorbidity index (36). Follow-up visits with study nurses and radiation oncologist were scheduled immediately at the end of the radiation therapy, 1 month later, and then every 6 months for the first 3 years followed by once a year until the end of the study (June 30, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Creating study-specific measures may not be possible, however, and investigators often apply measures in a manner at variance from how they were developed. 10,12,[16][17][18] In this study, we identified 4 administrative claims-based measures of comorbidity that have been used frequently in the health services literature to adjust for baseline health status and compared their performance in predicting 2 outcomes of importance to cancer care researchers-receipt of recommended adjuvant chemotherapy and mortality-among stage III colon cancer patients. We chose to study stage III colon cancer patients for several reasons.…”
mentioning
confidence: 99%
“…4,[6][7][8][9][10] Collectively these data provide evidence for a 2 to 8-fold elevated risk of CLL in case relatives.…”
Section: Familial Risks Of Chronic Lymphocytic Leukemiamentioning
confidence: 76%
“…3 Disease-specific comorbidity measures are developed and tested in a single disease population, and intended for use only in that setting. 8 They have a conceptual advantage in that they account for specific treatments and outcomes unique to the population of interest. 6 A major limitation in implementing either general or disease-specific measures is the data source used for their generation.…”
mentioning
confidence: 99%